Three-dimensional artificial transpiration for efficient solar waste-water treatment. Issue 1 (2nd May 2017) - Li, Xiuqiang; Lin, Renxing; Ni, George; Xu, Ning; Hu, Xiaozhen; Zhu, Bin; Lv, Guangxin; Li, Jinlei; Zhu, Shining; Zhu, Jia
Abstract: Solar steam generation is emerging as promising solar-energy conversion technology for potential applications in desalination, sterilization and chemical purification. Despite the recent use of photon management and thermal insulation, achieving optimum solar steam efficiency requires simultaneous minimization of radiation, convection and conduction losses without compromising light absorption. Inspired by the natural transpiration process in plants, here we report a 3D artificial transpiration device with all three components of heat loss and angular dependence of light absorption minimized, which enables over 85% solar steam efficiency under one sun without external optical or thermal management. It is also demonstrated that this artificial transpiration device can provide a complementary path for waste-water treatment with a minimal carbon footprint, recycling valuable heavy metals and producing purified water directly from waste water contaminated with heavy metal ions.